PROFIL SOSIAL EKONOMI MASYARAKAT PETANI KOPI ARABIKA DI DESA SUNGAI LINTANG KECAMATAN KAYU ARO BARAT - Sari, Desi Purnama (STKIP PGRI Sumbar, 2014)
This Study aims to obtain the data, process, analyze and discuss the Socio-economic Profile of Arabica Coffeeâs farmers society in District of Kayu Aro Barat Sungai Lintang Village of Kerinci Regency views of : 1) Basic needs, 2) Income, 3) Education, dan 4) Health. This study classified the type of descriptive research. Population in this study where all Arabica Coffeeâs farmers society in District of Kayu Aro Barat Sungai Lintang Village of Kerinci Regency at Jambi Province. The sample is taken with a total sampling with sample amounts to 47 arabica coffeeâs farmers. Data analysis techniques using a liker scale techniques. Collection of data using questionnaires or instruments. Result of study found that : 1) Condition Basic needs Arabica coffeeâs farmers was apparent from the clothing generally never buy clothes in 1 mount with the percentage of 42.55%, conditions sufficient food to meet their daily needs with the percentage of 82.24% boards are generally semi-permanent condition and completed 100% with the percentage of 42.56% which is very strong in the criteria. 2) Arabica Coffeeâs farmers income conditions are generally Rp2,000,000.- with 36.17%, and revenue per month generally Rp1,000,000.- side with percentage 53.19%, which is the sufficient criteria. 3) Educational conditions Arabica coffee farmers with the liker scale 37.16% which is at sufficient criteria. 4) Health conditions Arabica coffee farmers with the liker scale was 63.94% on robust criteria.